Using PhotoVoice to understand mindfulness in health care practitioners - Iram Osman; Veena Singaram (AOSIS, 2022)
Background: The disruptions of the coronavirus disease 2019 (COVID-19) pandemic have placed added stress on health care practitioners' (HCPs) mental health. Mindfulness-based interventions (MBIs) have been reported to increase the awareness of burnout and promote self-care practices that enhance mental well-being. Aim: To gain insight into the use of mindfulness through the lens of PhotoVoice on how HCPs reflected on their stressors and sense of self whilst working as frontline workers during the COVID-19 pandemic. Setting: This study was conducted online with HCPs working in South Africa during the first wave of COVID-19. Method: A four-week MBI intervention was implemented using Zoom. An exploratory qualitative analysis was conducted using a PhotoVoice methodology. Interpretative phenomenological analysis was used to generate themes. Fifty-five HCPs consented to participate in this study. Results: The major themes identified were operating on autopilot, feeling a sense of overwhelm because of COVID-19, using faith to cope and being able to attain a sense of self-compassion by the end of the intervention. Conclusions: Using visual representations, HCPs were able to share the development of their reperceived lived experiences of increased self-compassion as they navigated the dilemmas and disruptions of the pandemic. Contribution: A brief online MBI was impactful enough to show a reappraisal of the stressors of COVID-19, such that HCPs felt calmer, more competent and more compassionate. PhotoVoice methodology is recommended for future studies and mindfulness courses. It facilitates a deeper understanding of the practice of imbuing mindfulness and its impact on stressors and the self.